STATE AND RESPONSIBILITY FOR IMPLEMENTATION OF ISLAMIC LAW - Muhammad Yusuf (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2022)
For every Muslim, carrying out all the teachings of Islam in his life is an obligation. Among the aspects contained in Islamic teachings, one of which is related to law which has several parts. Among these sections there are certain parts of the law that cannot be implemented by the Muslim community without the involvement of the authorities, especially in this study is part of the jinayah law. However, in the application of the law of jinayah, there are many polemics in society, especially among non-Muslims because the law of jinayah is considered severe and what is regulated in the law of jinayah has different perspectives/judgments among them. This is one of the considerations that the government finds it difficult to accept the proposal for the implementation of the law of jinayah in Indonesian society. This study tries to see how the relationship between law and the state and how the obligations of the ruler in the implementation of Islamic law in Muslim society. This study aims to see the extent of the obligations of Muslim rulers in implementing Islamic law for their people or citizens and to also see the special character of the law of jinayah related to its implementation. The method used in this research is qualitative with a normative juridical approach.